Innovative Approaches to the Use of Artillery in Wildfire Suppression - Daniel Korec; Martin Blaha; Jiří Barta; Jaroslav Varecha (Fire, 2025)
The increasing frequency and intensity of wildfires in hard-to-reach and hazardous areas represents a significant challenge for traditional firefighting methods. Wildfires pose a growing threat to the environment, property, and human lives. In many cases, conventional suppression techniques prove ineffective, highlighting the need for innovative and efficient solutions. Recent fires in the Bohemian Switzerland National Park in the Czech Republic; the Los Angeles area in California, USA; and the southeastern region of South Korea have underscored the necessity for alternative wildfire mitigation strategies. This article explores the potential of employing military technologies, such as artillery systems and specialized munitions, in wildfire suppression. The analysis includes a review of previous experiments, the research into non-standard methods, and an assessment of the risks and limitations associated with these approaches. Based on the research and simulations, it was found that one salvo (eight rounds) of fire-suppressant shells can cover up to 650 m2 of terrain with suppressant. Finally, this article proposes a direction for further research aimed at integrating military and civilian technologies to enhance the effectiveness of wildfire response. This work contributes to the ongoing discussion on the integration of artillery capabilities into crisis management and provides a foundation for the future research in this field.